Viral Antibodies in Diabetes Mellitus. Issue 5671 (13th September 1969) - Gamble, D. R.; Kinsley, M. L.; FitzGerald, M. G.; Bolton, R.; Taylor, K. W.
Abstract : Sera from 123 patients with diabetes mellitus of recent onset, 155 patients with diabetes of more than two years' duration, and 250 normal persons were collected over a period of two and a half years. All sera were tested for neutralizing antibody to Coxsackie virus types B1–6, and a sample was tested for complement-fixing antibody to a number of viral, rickettsial, and mycoplasmal antigens. In diabetics of recent onset no evidence was found of any excess of antibodies to mumps virus or some common respiratory viruses. Insulin-dependent diabetes within three months of onset were found to have higher antibody titres to Coxsackie B virus, particularly of type B4, than either normal subjects or patients with diabetes of longer duration.